Drying and characterization of red beet color liquid process waste to develop a novel bulking agent - Atalar, Ilyas; Konar, Nevzat; Dalabasmaz, Sevim; Saygin Kantemur, Pervin; Han, Emine (Journal of Cleaner Production, 2024)
For cleaner and sustainable production, industrial food waste reuse studies are great of importance. In this study, to develop a novel bulking agent from the liquid wastes of colorant production processes obtained from red beet extract (RBW), an optimization study with an 18-point experimental point was performed in a pilot spray dryer by using maltodextrin as a carrier material for drying. The spray drying inlet temperature (120–140 °C) and the ratios of carrier agent (10%–25%) and liquid waste (75%–90%) in the feed solution were independent variables. Optimization responses were drying yield (44.4–86.6%) and moisture content (1.39–3.89 g/100 g). In addition, physicochemical (water activity, color, pH), particle size distribution, and various powder characteristics of the samples were investigated. Significant models for responses were determined (P < 0.05). The optimum conditions (Desirability: 0.876) for RBW drying were determined and validated as 120 °C spray dryer inlet temperature, and feed solution containing 90% RBW and 10% maltodextrin in dry matter. As a result, powders obtained from RBW have the potential to be used as a bulking agent in food formulations due to their composition and low moisture content, water activity and drying yield (>80.0%). According to our results, it may be possible to prevent the release of RBW which has high COD and BOD values and to decrease the production and waste treatment costs of the colorant industry. However, the limitations of the novel bulking agent as residual pigments and total ash content should be considered for further food applications.
CRIS-Team Scopus Importer:2025-02-04
Keywords: Beta vulgaris; Bulking agent; Optimization; Spray drying